Role of Toll-like Receptors in Adjuvant-Augmented Immune Therapies. Issue 1 (2006) - Seya, Tsukasa; Akazawa, Takashi; Tsujita, Tadayuki; Matsumoto, Misako
Abstract : Effective therapeutic vaccines contain two primary constituents, antigen and adjuvant. Adjuvants consisting of microbial pattern molecules play a central role in vaccination. Successful vaccine requires efficient induction of antibody (Ab), type I interferons (IFN), cytokines/chemokines, cytotoxic T lymphocytes (CTL) and/or NK cells. Toll-like receptors (TLRs) in myeloid dendritic cells (mDC) essentially act as adjuvant receptors and sustain the molecular basis of adjuvant activity. Current consensus is that TLRs and their adapters introduce signals to preferentially induce IFN-α/β, chemokines and proinflammatory cytokines, and mature mDC to augment antigen presentation. Although most of these data were obtained with mice, the results are presumed to be adaptable to humans. Whenever TLR pathway is activated in mDC, NK and/or CTL activation is promoted. For induction of antigen-specific CTL toward phagocytosed material, cross-priming must be induced in mDC, which is also sustained by TLR signaling in mDC. Since the TLR responses vary with different adjuvants, mDC functions are skewed depending on adjuvant-specific direction of mDC maturation. It appears that the directed maturation of mDC largely relies on selection of appropriate sets of TLRs and their adapter signaling pathways. Synthetic chimera molecules consisting of TLR agonists and target antigens are found to be effective in induction of CTL to eliminate target cells in vivo . Here, we review the role of human TLRs and adapters in a variety of host immune responses. We will also describe the relevance of adjuvants in the manipulation of receptors and adapters in vaccine therapy.